Coding and Reimbursement for Cochleotoxicity and Vestibulotoxicity Services - Abel, Debra (Seminars in Hearing, 2019)
Because of the ICD-10 disease coding system transition that occurred in the United States in 2015, coding and billing for services on behalf of patients who experience cochlear and/or vestibular toxicity may be daunting and misunderstood. Coding and billing for any audiology procedure can be compelling; choosing the appropriate codes for these specific patients is critical not only for payment for services rendered but also for the national and global implications, given their utilization is tracked for mortality and morbidity statistics and potential policies.
Keywords: ototoxic hearing loss; anti-neoplastics; aminoglycosides; medical record documentation